A Therapeutic Sheep in Metastatic Wolf’s Clothing: Trojan Horse Approach for Cancer Brain Metastases Treatment - Liu, Hai‑jun; Wang, Mingming; Shi, Shanshan; Hu, Xiangxiang; Xu, Peisheng (Nano-Micro Letters, 2022)
Early-stage brain metastasis of breast cancer (BMBC), due to the existence of an intact blood–brain barrier (BBB), is one of the deadliest neurologic complications. To improve the efficacy of chemotherapy for BMBC, a Trojan horse strategy-based nanocarrier has been developed by integrating the cell membrane of a brain-homing cancer cell and a polymeric drug depot. With the camouflage of a MDA-MB-231/Br cell membrane, doxorubicin-loaded poly (D, L-lactic-co-glycolic acid) nanoparticle (DOX-PLGA@CM) shows enhanced cellular uptake and boosted killing potency for MDA-MB-231/Br cells. Furthermore, DOX-PLGA@CM is equipped with naturally selected molecules for BBB penetration, as evidenced by its boosted capacity in entering the brain of both healthy and early-stage BMBC mouse models. Consequently, DOX-PLGA@CM effectively reaches the metastatic tumor lesions in the brain, slows down cancer progression, reduces tumor burden, and extends the survival time for the BMBC animal. Furthermore, the simplicity and easy scale-up of the design opens a new window for the treatment of BMBC and other brain metastatic cancers. Highlights: 1 DOX-PLGA@CM employs the whole set of membrane molecules of a brain-homing metastatic breast cancer cell optimized through a natural selection process. Thus, the hetero and multivalent effects of these molecules greatly facilitate the nanoparticle crossing the blood-brain barrier. 2 Attributed to the homotypic effect of the nanocarrier, DOX-PLGA@CM shows stronger anticancer efficacy than free DOX for its parenteral cells. 3 DOX-PLGA@CM effectively reaches the metastatic tumor lesions in the brain, and slows down the progression of brain metastatic breast cancer.